The Anxiety Dilemma: Locating the Western Balkans in the Age of Anxiety - Cupać, Jelena (Journal of Regional Security, 2020)
The paper seeks to locate the Western Balkans in the current age of anxiety. By using the concept of ontological security as its overarching theoretical frame, the paper first develops a concept of anxiety dilemma. The anxiety dilemma refers to a situation in which a social order that provides one group of people with a sense of ontological security is a perceived source of anxiety for the other group and vice versa. The paper proposes that such a dilemma characterizes the present age of anxiety. Trapped in this dilemma are the proponents and the contesters of the liberal (international) order and globalization, often referred to in the literature as cosmopolitans and communitarians. The paper argues that the Western Balkan countries occupy an ambivalent position in this anxiety dilemma. Their governments combine liberal-democratic justification with autocratic tendencies. The paper discusses how the Western Balkans came to occupy this position. It singles out four reasons: (1) the region’s authoritarian legacy; (2) ethnonationalism coupled with state- and nation-building projects; (3) search for external legitimacy; and (4) the EU’s abandonment of the inextricable link between peace and democracy. The case of the Western Balkans yields another important observation: that local anxiety dilemmas are nested in global anxiety dilemma. The paper makes two contributions. The first one is theoretical, and it consists of furthering the concept of ontological security such that it theorizes ontological security as a systemic inter-group phenomenon. The second contribution is analytical, and it consists in locating the Western Balkans in the ongoing struggles over globalization and the liberal (international) order.